THE STUDENTS’ PERCEPTIONS TOWARD QUIZIZZ AS AN ONLINE LEARNING MEDIA - Herlina; Yuli Rahmawati (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study discusses about the importance of media instrument media to support teaching and Learning English enjoyable. The goal is to find out how students' perception toward the use of Quizizz as teaching media. Qualitative research methods and open questionnaire as the research instrument were used The data Questionnaire where come from the participant’s answer that would be described and interpreted. As the result of this study there was two perceptions: a positive perception and a negative perception. It is hoped that this study will motivate teachers and other researchers to investigate further, related to improve the use of teaching media.